Turkish and European Union Political Maneuvers in the Syrian Conflict - Juasari, Itra; Walidin, Muhammad; Mikail, Kiki (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study delves into the political maneuvers undertaken by Turkey and the European Union within the Syrian conflict. The initiation of these maneuvers stemmed from the construction of a gas pipeline in Syria. The research aims to examine the implications of these maneuvers on political stability and security in Syria, with a particular focus on understanding the Turkish and European Union perspectives. The study employs two theoretical frameworks, namely national interest theory and geopolitical theory. Qualitative methods were employed, leveraging primary data obtained through interviews with geopolitical expert Mrs. Dina Y Sulaeman, Director of the Indonesia Center for Middle East Studies (ICMES), and Dr. Muhammad Reza Ebrahimi, an observer of Middle Eastern politics at the Islamic Culture and Relations Organization. Additionally, secondary data was gathered from theses, journals, and research websites pertinent to the study. Findings reveal that both Turkey and the European Union pursued political maneuvers in Syria driven by their economic and political interests. These maneuvers included efforts surrounding the construction of a gas pipeline in 2015 and support for opposition groups aiming to overthrow the Bashar Al Assad regime. However, the response from the Syrian government to internal opposition and demonstrations was met with military deployment and suppression, reflecting Al Assad's confidence in his government's ability to withstand challenges from opposition forces.